2014
DOI: 10.2147/ndt.s62728
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of verbal fluency in patients with diffuse brain injury over time

Abstract: BackgroundDiffuse axonal injury (DAI), a common cause of neurological sequelae in patients with traumatic brain injury (TBI), is considered one of the most prevalent forms of primary neuronal injury in patients with severe TBI. Cognitive deficits induced by DAI can persist over time, especially following moderate or severe injuries. The aim of the present study was to compare verbal fluency (VF) performance at 6 and 12 months after the trauma in a same group of patients with DAI.MethodsEighteen patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Concerning the research designs and research topics, the majority of studies (18 studies) compared word generation performance of a clinical group either to that of a control group or to normative data, or to another (clinical) group (Bittner & Crowe, 2006;Cralidis & Lundgren, 2014;Crawford et al, 2007;Crowe, 1996 Zakzanis et al, 2011Zakzanis et al, , 2013Zaninotto et al, 2014). In two studies, word generation performance is examined in relation to another performance measure (e.g., cognitive skills, naming) within a group of participants (Bittner & Crowe, 2007;Haggard, Cockburn, Cock, Fordham, & Wade, 2000).…”
Section: Use Of Additional Performance Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning the research designs and research topics, the majority of studies (18 studies) compared word generation performance of a clinical group either to that of a control group or to normative data, or to another (clinical) group (Bittner & Crowe, 2006;Cralidis & Lundgren, 2014;Crawford et al, 2007;Crowe, 1996 Zakzanis et al, 2011Zakzanis et al, , 2013Zaninotto et al, 2014). In two studies, word generation performance is examined in relation to another performance measure (e.g., cognitive skills, naming) within a group of participants (Bittner & Crowe, 2007;Haggard, Cockburn, Cock, Fordham, & Wade, 2000).…”
Section: Use Of Additional Performance Measuresmentioning
confidence: 99%
“…Out of the 20 studies including at least one additional measure, 14 studies reported a sufficient number of data points in order to calculate effect sizes. Due to a lack of sufficient data we could not include the additional measures word frequency and classification of word class in our effect size Gruen et al, 1990;Johnson et al, 2012;Kavé et al, 2011;Kessler et al, 1997;Raskin & Rearick, 1996;Sperinck & Picciotto, 1999;Velázquez-Cardoso et al, 2014;Zakzanis et al, 2011Zakzanis et al, , 2013Zaninotto et al, 2014 .55…”
Section: Explanatory Power Of Additional Performance Measuresmentioning
confidence: 99%
See 3 more Smart Citations